A tool for mainstreaming peacebuilding in climate-adaptation efforts: Evidence and processes. A framework and a safeguarding approach for conflict-sensitive and peace responsive climate action: The Climate-Security Sensitivity Tool (CSST) - Sarzana, Carolina; Melgar, Adriana; Meddings, George; Johnson, Vincent; Läderach, Peter R.D.; Pacillo, Grazia (CGIAR FOCUS Climate Security, 2023)
This paper aims to provide a theoretical and conceptual framework to distil the complex problem around linking climate adaptation, conflict sensitivity and peacebuilding, with the final goal of operationalizing it into a practical tool. By linking such fields of practice, it provides a scheme for climate action practitioners to better identify and address contextual drivers of conflict and insecurity while advancing peacebuilding processes. This paper lays the theoretical groundwork for this model and presents an actionable ex-ante tool for prioritizing mechanisms to address contextual conflict and insecurity drivers when designing climate adaptation interventions.